Changes in segmentation and setation along the anterior/posterior axis of the homonomous trunk limbs of a remipede (Crustacea, Arthropoda) - Viacheslav N. Ivanenko (PeerJ, 2016)
This study describes the segmentation and setation at different developmental stages of the homonomous trunk limbs of the remipede Speleonectes tulumensis Yager, 1987 collected in anchialine caves of the Yucatan Peninsula. Most homonomous trunk limbs originate ventrolaterally and are composed of two protopodal segments, three exopodal segments and four endopodal segments; contralateral limb pairs are united by a sternal bar. However, the last few posterior limbs originate ventrally, are smaller sized, and have regressively fewer segments, suggesting that limb development passes through several intermediate steps beginning with a limb bud. A terminal stage of development is proposed for specimens on which the posterior somite bears a simple bilobate limb bud, and the adjacent somite bears a limb with a protopod comprised of a coxapod and basipod, and with three exopodal and four endopodal segments. On each trunk limb there are 20 serially homologous groups of setae, and the numbers of setae on different limbs usually varies. These groups of setae are arranged linearly and are identified based on the morphology of the setae and their position on the segments. The number of setae in these groups increases gradually from the anterior homonomous limb to a maximum between limbs 8–12; the number then decreases sharply on the more posterior limbs. Changes in the number of setae, which reach a maximum between trunk limbs 8–12, differ from changes in segmentation which vary only over the last few posterior trunk limbs. Following a vector analysis that identified a spatial pattern for these 20 groups of setae among the different homonomous limbs, the hypothesis was confirmed that the number of setae in any given group and any given limb is correlated with the group, with the position of the somite along the body axis, and with the number of somites present on the specimens. This is the first vector analysis used to analyze a pattern of developmental changes in serially homologs of an arthropod. Development of remipede limbs are compared and contrasted with similar copepod limbs. Architecture, particularly the sternal bar uniting contralateral limb pairs, proposed as homologous, and development of trunk limb segmentation of the remipede is generally similar to that of copepods, but the remipede limb differs in several ways including an additional endopodal segment, the proximal, that appears simultaneously with the protopod during development.